RETENTION OF MINI SCREWS IN ORTHODONTICS – A COMPARATIVE IN VITRO STUDY ON THE VARIABLES: RETENTION OF MINISCREWS - Asok, Nikhil (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
Objectives: To correlate between the different lengths, angles of insertion and the mini-implant material and find out the most retentive combination.Materials and methods: 48 mini-implants (24 Titanium and 24 stainless steel) of lengths 6mm, 8mm and 1.5 mm diameter were inserted into humerus bone of goat at two different angulations, 600 and 900. To insert the mini-implant in the respective angulations, custom made template was made and the angles were confirmed with digital radiographs. Force was applied on to the mini-implants with a universal testing machine and the compressive load to failure was measured.Results: Results revealed that stability of the implant was positively correlating with the length of implant. A perpendicular angulation produced more stability. Moreover, titanium mini-implants had more resistance to compressive load than stainless steel mini-implants.Conclusion: Length of mini-implant, its angulation in the bone and the material of mini-implant were factors affecting its stability. In this study, titanium mini-implant of 8mm length angulated at 900 were stable than their counterparts.
Keywords: miniscrews; study on miniscrew variables; retention of miniscrews; miniscrews orthodontics